The Relationship of Glucokinase Activator–induced Hypoglycemia with Arteriopathy, Neuronal Necrosis, and Peripheral Neuropathy in Nonclinical Studies. (June 2014) - Pettersen, John C.; Litchfield, John; Neef, Natasha; Schmidt, Stephen P.; Shirai, Norimitsu; Walters, Karen M.; Enerson, Bradley E.; Chatman, Linda A.; Pfefferkorn, Jeffrey A.
Glucokinase activators (GKAs) are being developed for the treatment of type 2 diabetes. The toxicity of 4 GKAs (PF-04279405, PF-04651887, piragliatin, and PF-04937319) was assessed in mice, rats, dogs, and/or monkeys. GKAs were administered for 2 to 8 weeks. Standard endpoints, glucose, and insulin were assessed. All compounds produced varying degrees of hypoglycemia in all species. Brain neuronal necrosis and/or peripheral neuropathy were observed with most compounds. These findings are consistent with literature reports linking hypoglycemia with nervous system effects. Arteriopathy, mainly of cardiac vessels, was observed at a low frequency in monkey and/or dog. Arteriopathy occurred only at doses that produced severe and prolonged periods of repeated hypoglycemia. Since this lesion occurred in multiple studies with structurally distinct GKAs, these results suggested arteriopathy was related to GKA pharmacology. The morphological characteristics of the arteriopathy were consistent with that produced by experimental catecholamine administration. We hypothesize that the prolonged periods of hypoglycemia resulted in increased local and/or systemic concentrations of catecholamines via a counterregulatory and/or stress-related mechanism. Alternatively, prolonged hypoglycemia may have resulted in endothelial dysfunction leading to arteriopathy. This risk can be managed in human patients in clinical studies by careful glucose monitoring and intervention to avoid prolonged episodes of hypoglycemia.